THE INFLUENCE OF BRAND IMAGE AND BRAND TRUST ON SATISFACTION AND LOYALTY ON TELEVISION PRODUCTS TOSHIBA SURABAYA REGION - Bagus Ranu Irwanto; Ani Wulandari (NAROTAMA UNIVERSITY, Indonesia, 2020)
Given the intense level of competition in the electronics business in Indonesia, the company continues to strive to increase market share and reach new customers and no less importantly the company must work hard in maintaining customer loyalty, including Toshiba products. However, the Top Brand Index value for Toshiba Television products in Indonesia from 2012-2014 has decreased. The decline is not profitable for Toshiba products because this will have an impact on lowering revenue and deteriorating image and customer satisfaction. Based on these problems, this study aims to determine the effect of brand image and brand trust on satisfaction and loyalty in the Surabaya area of ​​Toshiba television products. The population in this study were customers of Toshiba Television products, Surabaya branch, samples were taken were 96 people. This study uses a path analysis model (path analysis). The path analysis technique is one of the statistical analysis techniques used in quantitative research. Based on the test results using the analysis to test the effect of brand image, brand trust, and satisfaction with brand loyalty, the following conclusions can be drawn: Brand Image has a positive and significant effect on Customer Satisfaction, Brand Trust has a positive and significant effect on Customer Satisfaction, Brand Image has a positive and significant effect on customer loyalty, brand trust has a positive and significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, brand image on customer loyalty through customer satisfaction is more dominant than brand trust on customer loyalty through customer satisfaction.